Women Participation In Politics And Use Of Digital Technology To Access Political Information - Yudiana Indriastuti (Jurnal Ilmu Komunikasi, 2018)
The presence of digital technology can eliminate cultural barriers and personal barriers to women to participate in politics.The purpose of this study is to identify women's political participation. Women as research subjects here are voters / voters in elections who are not members of political parties or other political organizations. The method to be used in this research is explorative qualitative research methods. The findings in this study are, (1) Women access political information unintentionally when information about politics appears in the timeline and they do not participate in politics (2) Women actively access Information, discuss politics and they do not participate in politics (3) Women access political information unintentionally when information about politics appears in the timeline and they participate in politics because of the couple's motivation for reasons that their voices are not misused.